Search Region of Origin Honey Bee A. mellifera in Indonesia Region Using Mitochondrial DNA intergenic cox1/cox2 - Hidayat, Mohamad Rusdi (Balai Riset dan Standardisasi Industri Pontianak, 2011)
Apis mellifera is a favourite honey bee for the beekeepers throughout many countries. This species comprise of 24 subspecies. Based on phylogeography and morphometric evidences, these subspecies have been grouped into four lineage; namely the African (A), Western and Northern Europe (M), Southeastern Europe (C), and Near Eastern (O). Apis mellifera have been imported to Indonesia since 1972, and mostly from Australia. However, until recently there are no data about the A. mellifera subspecies and the origin. Therefore the objective of this research is to determine the lineage of A. mellifera in Indonesia based on mtDNA intergenic region between cox1/cox2 genes. In this region there are two DNA fragments, P and Q fragnant, that can be used to determine the A. mellifera lineage. The methodology used consist of samples collection, DNA isolation, DNA amplification, DNA restriction using DraI enzyme, DNA sequencing, and DNA alignment using Clustal X and MEGA spftwares. DNA fragment amplified by using E2 and H1 primer revealed a 863 bp. Digestion of the region with the DraI restriction enzyme revealed one haplotype, which consist of five DNA fragments. Based on DNA sequences and DNA alignment, A. mellifera in Indonesia was homologue with the C lineage. Its subspecies is A. m. ligustica that lived natively in Italy, they were imported to Indonesia from Australia